Quantity of non-point sources of nitrogen and phosphorus from surface runoff to Lam Plai Mat reservoir, Nakhon Ratchasima province (Thai) - Noinumsai, Napat (Asia-Pacific Journal of Science and Technology, 2017)
Lam Plai Mat reservoir has a catchment area of 480 Km2 and consists of 7 main streams, Lam Saikong, Lam Mafai, Sap Angthong, Huay Pong Katak, Huay Nong Plalai, Huay Koom and Lam Satein and 21 sub - streams. Typically, this reservoir can store surface runoff of about 115 Mm 3 yr -1. This research studied non-point sources of nitrogen and phosphorus and water quality in Lam Plai Mat reservoir. The water samples were collected from 11 points along 7 main streams during November 2005-October 2006. It was found that total nitrogen (TN) and total phosphorus (TP) of 47,338.08 Kgyr-1 and 2,306.35 Kgyr-1 were discharged into the reservoir. The N:P ratio was 20.53. The data shows that nitrogen and phosphorus influence primary production of chlorophyll A in the main streams that runoff into the reservoir at an average of 3.7131 mgl-1. The total phosphorus is the limiting factor, showed in a positive correlation with rain conditions.